1989
DOI: 10.1210/endo-124-6-2666
|View full text |Cite
|
Sign up to set email alerts
|

Peptidylarginine Deiminase in Rat Pituitary: Sex Difference, Estrous Cycle-Related Changes, and Estrogen Dependence*

Abstract: We have found notable sex difference in peptidylarginine deiminase (EC 3.5.3.15) in rat pituitaries. Pituitaries collected from 3-week to 6-month-old male rats, and those from 3-week-old females showed negligible enzyme activities. The enzyme activity of female pituitaries increased markedly by 2 months, and even further by 6 months of age. Measurements of the enzyme activity around the estrous cycle revealed its characteristic change, being high in the proestrus and estrus, and low in the metestrus and diestr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
33
0

Year Published

1990
1990
2013
2013

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 54 publications
(35 citation statements)
references
References 26 publications
1
33
0
Order By: Relevance
“…Furthermore, our recent studies have demonstrated that the expression of this enzyme in the uterus is controlled by steroid hormones [ 151. Estrous-cycle-dependent changes of this enzyme in the rat pituitary gland have also been reported by Senshu et al [16], and they showed that such changes were partly under the control of estrogen [16-181. Among the tissues so far tested, only the uterus [lS] and the pituitary gland [16, 181 display changes in the level of this enzyme in response to steroid hormone administration, indicating that the hormonal regulation is not systemic. Thus, peptidylarginine deiminase is of considerable interest for studies on the regulatory mechanisms involved in the tissue-specific expression of genes.…”
mentioning
confidence: 61%
“…Furthermore, our recent studies have demonstrated that the expression of this enzyme in the uterus is controlled by steroid hormones [ 151. Estrous-cycle-dependent changes of this enzyme in the rat pituitary gland have also been reported by Senshu et al [16], and they showed that such changes were partly under the control of estrogen [16-181. Among the tissues so far tested, only the uterus [lS] and the pituitary gland [16, 181 display changes in the level of this enzyme in response to steroid hormone administration, indicating that the hormonal regulation is not systemic. Thus, peptidylarginine deiminase is of considerable interest for studies on the regulatory mechanisms involved in the tissue-specific expression of genes.…”
mentioning
confidence: 61%
“…Using pituitary lysates, investigators noticed a strong sexual dimorphism with a high level of PAD activity in the female rat pituitary, while little enzymatic activity was seen in the pituitary gland from males. Negligible PAD enzymatic activity was detected in 3-week old female pituitary, but by about 4 months of age, activity increased substantially, suggesting that sexual maturation contributes to PAD expression [58]. In rats, serum estrogen (17β-estradiol) concentration varies during the estrous cycle, gradually increasing during metestrus, peaking at proestrus, followed by a sharp decrease during estrus [59].…”
Section: Pituitarymentioning
confidence: 99%
“…Estrous cycle-staged rats showed a two-fold higher PAD activity level in pituitary lysates during proestrus and estrus than during metestrus and diestrus stages. Thus, the rise in 17β-estradiol serum levels just prior to increased PAD activity levels suggests that the fluctuations of the hormone during the estrous cycle plays an important role in PAD expression in the pituitary [58].…”
Section: Pituitarymentioning
confidence: 99%
See 1 more Smart Citation
“…In vitro citrullination is only detectable in the presence of high calcium concentration (11) but in healthy conditions, its concentration range is 10 -8 -10 -6 M, so PADs are inactive (12).This suggests that the citrullination process happens only under 'extreme' conditions, such as during apoptosis or terminal differentiation of the epidermis. PADs are enzymes primarily involved in apoptotic and differentiation events in physiological conditions and recently they have also been involved in other cellular processes, such as gene regulation (13,14).…”
Section: Introductionmentioning
confidence: 99%